EFEKTIVITAS PROGRAM PELATIHAN PEGAWAI DI DINAS KETENAGAKERJAAN DAN TRANSMIGRASI PROVINSI MALUKU UTARA - DJABAR, ROY ARISANDY; RORONG, ARIE; KOLONDAM, HELLY (Sam Ratulangi University, 2020)
The implementation of education and training for employees has not been maximized and the limitations ofteaching staff or trainers in the education and training process. Based on the background of the problem, thisstudy aims to determine the effectiveness of the employee training program at the Office of Manpower andTransmigration of North Maluku Province.The method in this research is qualitative research to explain a phenomenon in depth by means of collectingdata as deep as possible, which shows the importance of the depth and detail of the data being studied. Datacollection techniques obtained through: Interview; Direct Observation and DocumentationThe results showed that the employee training program was not yet fully effective because employees who hadenthusiasm and willingness to attend training seemed to have a good reaction and for employees who thoughtthat training was just a work program that had to be realized showed a bad reaction. The learning dimensionis concluded to be effective in developing concepts and work knowledge and in building work relationships andutilizing work facilities. Employee training programs through the dimensions of behaviors can be concludedas effective as seen in changes in behavior in understanding subordinates, communicating and behaving andhelping each other. Employee training programs through the organizational results dimension (organizationalresults) are concluded to be effective in terms of good impact in relationships with leaders, staff and workpartners, accelerating the achievement of vision and mission as well as in responsibility and work spirit.Key words: effectiveness; Training Program, Employees